Highly resistive C-doped hydride vapor phase epitaxy-GaN grown on ammonothermally crystallized GaN seeds. (14th December 2016) - Iwinska, Malgorzata; Piotrzkowski, Ryszard; Litwin-Staszewska, Elzbieta; Sochacki, Tomasz; Amilusik, Mikolaj; Fijalkowski, Michal; Lucznik, Boleslaw; Bockowski, Michal
Abstract: GaN crystals were grown by hydride vapor phase epitaxy (HVPE) and doped with C. The seeds were high-structural-quality ammonothermally crystallized GaN. The grown crystals were highly resistive at 296 K and of high structural quality. High-temperature Hall effect measurements revealed p-type conductivity and a deep acceptor level in the material with an activation energy of 1 eV. This is in good agreement with density functional theory calculations based on hybrid functionals as presented by the Van de Walle group. They obtained an ionization energy of 0.9 eV when C was substituted for N in GaN and acted as a deep acceptor.